Efeitos da administração intragástrica de Bifidobacterium longum subsp. infantis CHCC2228 em um modelo murino agudo de colite ulcerativa induzida por sulfato sódico de dextrana (DSS) - Samir de Deus Elian Andrade (2013)
IBDs are chronic inflammatory conditions, characterized by remissions and relapses, whose main manifestations are ulcerative colitis and Crohn's disease. Ulcerative colitis, one of the main forms of IBDS has as standard treatment the use of corticosteroids and anti-inflammatory drugs. The use of antibiotics has also been reported, but the possible adverse effects must be taken into consideration and thus the use of probiotics emerges as a real possibility. In this study, we evaluated the possibility of using Bifidobacterium longum subsp. infantis CHCC2228 as treatment for ulcerative colitis in a murine model. For induction of colitis in female BALB/c mice, we replace the water by a 3.5% DSS (dextran sodium sulphate) solution for 7 days. During this period, the animals were evaluated for weight variation, fecal consistency and presence of bleeding in feces. On the seventh day, the animals were euthanized to collect the organs to the histological analysis of the liver, small intestine and colon. Other experiments were done, as: dosage of sIgA in the small intestine; evaluation of the intestinal permeability; indirect evaluation of the infiltration of eosinophils, neutrophils and macrophages by measuring their specific enzymes EPO (eosinophil peroxidase), MPO (myeloperoxidase) and NAG (N-acetyl-glucosaminidase); dosage of the cytokines KC and Eotaxin-1; evaluation of the permeability and oxidative stress in the intestine. Treatment with the probiotic resulted in clinical improvement of animals. The histological and morphometric analyzes showed a reduction of lesions and edema in the animals, but there was no increase in the production of mucin. The dosage of sIgA was significantly higher in the colitis group and reduced in the group treated with the probiotic. There was also a reduction in the inflammation of the colon, as indicated by the reduction of EPO and MPO activity, but no change in the activity of NAG. The intestinal permeability, which is typically increased during the onset of IBD, was reduced after treatment with bifidobacteria. There were no differences on rates of reactive oxygen species (ROS) generation. Based on these data it can be concluded that the bacterium B. longum subsp. infantis CHCC2228 has probiotic potential for the treatment of ulcerative colitis, but further studies should be conducted in order to verify the mechanisms of action of the bacterium.